21.5k views
1 vote
(-2,1); m = -3

My answer was Y = -6x + 1 and here's my equation.
Formula = Y - Y1 = m ( X - X1 )

1. Y - 1; -3 ( X - - 2 )
2. Y - 1; -3 ( X + 2)
3. Y - 1; -6X
4. Y - 1 = -6x Single out they Y so add 1 to both sides
5. Y = -6x + 1
And that's it I need help understanding it a bit and I need to know if I got my answer right if possible thank you!!​

User Worgon
by
6.0k points

2 Answers

2 votes

Answer:

your answer's correct!!

Explanation:

User Shine
by
6.1k points
3 votes

Answer:

I dont know if this is much help but I asked my mom to review it as she said it was correct. :)

User Desimusxvii
by
5.7k points